The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.20474/jabs-7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ant fragility and cross-cultural adaptability on employee engagement: The moderated mediation role of perceived insider status

Abstract: The purpose of the study was to examine the in luence of antifragility and cross-cultural adaptability on employee engagement, directly and in the moderated mediation role of perceived insider status. A self-designed questionnaire was utilized to collect data from 207 employees from Land Record Department, Punjab, Pakistan. The collected data was analysed through con irmatory factor analysis and structural equation modelling technique by utilizing AMOS as well as the moderating effects were evaluated through u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…It is acceptable that each religion contains a belief and ritual that determines and limits its own sporting activities. For example, the bullfighting competitions practiced in Spain are not accepted in Islam (Cengiz & Taşmektepligil, 2016;Saira et al, 2021).…”
Section: Islam and Sportsmentioning
confidence: 99%
“…It is acceptable that each religion contains a belief and ritual that determines and limits its own sporting activities. For example, the bullfighting competitions practiced in Spain are not accepted in Islam (Cengiz & Taşmektepligil, 2016;Saira et al, 2021).…”
Section: Islam and Sportsmentioning
confidence: 99%
“…Thus, the study on leadership must consider the correlations between variables at different levels. The existing studies have shown that the transformational leadership could affect the dependent variables such as intention of resignation and OCB (Virgiawan et al, 2021 ), and could affect the organizational contextual variables (Saira et al, 2021 ). Therefore, through multi-level research, employees' perceptions of leaders can be aggregated to the group level and their relationship with organizational commitment can be tested (Tremblay et al, 2019 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%